Human Capital in the Digital Age: Navigating Talent Retention and Upskilling Strategies for Global Competitiveness - Setyanti, Sri Wahyu Lelly Hana; Faliza, Nur; Rustandy, Andy (SAFE-Network, 2025)
In the context of rapid digital transformation, human capital has become a central pillar of organizational resilience and global competitiveness. This study employs a Systematic Literature Review (SLR) of 61 peer-reviewed articles published between 2018 and 2024 to examine contemporary strategies in talent retention and upskilling within digitally evolving workplaces. The findings reveal five dominant themes: talent retention strategies, upskilling and reskilling initiatives, digital HRM systems, employee engagement, and global workforce agility. These themes highlight the growing convergence between strategic HR practices and technological advancement. Organizations that integrate personalized learning pathways, data-driven decision-making, and inclusive talent development frameworks demonstrate greater adaptability and innovation. However, the review also uncovers regional disparities, implementation gaps, and the need for culturally responsive leadership. This study contributes to the theoretical enrichment of digital-era HRM and provides practical insights for policymakers and organizational leaders aiming to future-proof their workforce through aligned and agile human capital strategies.